The role of visualization in learning a foreign language - Elena V. Revina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article, the necessity to introduce visual aids to improve the effectiveness of the learning process is actualized. It is noted that the correct use of visualization is a means of gaining knowledge and makes it easier to remember the material. A number of modern methods of teaching a foreign language are distinguished and a description of possibilities of various visual aids is given in detail. The authors come to the conclusion that it is expedient to use visualization in the educational process, the effectiveness of which is confirmed by the growing cognitive activity of students, the possibility of individualizing the learning process, raising the level of positive motivation of future specialists.